Os arquivos do luto e as lições patéticas: uma educação sentimental em Anne Carson - Fernandes, Rafael Zacca (eLyra, 2022)
This article’s goal is to demonstrate Anne Carson’s practice of translation as a research activity in the “archives of grief”. It explains how this research results not only in products (the translated texts), but also in a set of “pathetic lessons”, teaching something about the pathos and reinforming the ethos. The article also includes an exposition on Carson’s rereading of Walter Benjamin’s theory of the translation, with which she conceives translation as a hearing of the original’s ruin. The object of analysis includes some of Carson’s essays and some of her translations of classical tragedies, the ones in Grief Lessons, with Euripides plays, as well as Antigonick, Carson’s translation of Sophocles’ Antigone.